Gymnastic Athletes Motivation: Study of Pekan Olahraga Provinsi Riau - Puja Sri Syahfitri; Agus Sulastio; Adi Wijayanto (CV. FOUNDAE, 2022)
The problem in this study is that the portion of mental training given to athletes is not well designed. The results of the athlete's performance are much less consistent with what was found that motivational factors were the cause of weak drive during the practices. This research aimed to establish the motivation of Riau Gymnastics athletes. The population consisted of 16 gymnastics athletes in Kuantan Singingi Regency using a total sampling technique of 16 athletes. The instrument used in this research is a questionnaire. Based on the results of the questionnaire, it was determined that the performance score percentage of two athletes (12.50 percent) was in the excellent category, eight athletes (50 percent) were in the high category of motivation, and one athlete (6.25 percent) had poor motivation. Based on the average score, the motivation of the Riau Gymnastics athletes to face the Porprov X Kuantan Singingi is in the moderate category because the psychological aspects are not paid enough attention to by the coach when coaching the training program.